Crack Propagation Behavior Modeling of Bonding Interface in Composite Materials Based on Cohesive Zone Method - Yulong Zhu; Yafen Zhang; Lu Xiang (Buildings)
Wood, steel, and concrete constitute the three predominant structural materials employed in contemporary commercial and residential construction. In composite applications, bond interfaces between these materials represent critical structural junctures that frequently exhibit a reduced load-bearing capacity, rendering them susceptible to the initiation of cracks. To elucidate the fracture propagation mechanisms at composite material interfaces, this study implements the cohesive zone method (CZM) to numerically simulate interfacial cracking behavior in two material systems: glued laminated timber (GLT) and reinforced concrete (RC). The adopted CZM framework utilizes a progressive delamination approach through cohesive elements governed by a bilinear traction–separation constitutive law. This methodology enables the simulation of interfacial failure through three distinct fracture modes: mode I (pure normal separation), mode II (pure in-plane shear), and mixed-mode (mode m) failure. Numerical models were developed for GLT beams, RC beams, and RC slab structures to investigate the propagation of interfacial cracks under monotonic loading conditions. The simulation results demonstrate strong agreement with experimental cracking observations in GLT structures, validating the CZM’s efficacy in characterizing both mechanical behavior and crack displacement fields. The model successfully captures transverse tensile failure (mode I) parallel to wood grain, longitudinal shear failure (mode II), and mixed-mode failure (mode m) in GLT specimens. Subsequent application of the CZM to RC structural components revealed a comparable predictive accuracy in simulating the interfacial mechanical response and crack displacement patterns at concrete composite interfaces. These findings collectively substantiate the robustness of the proposed CZM framework in modeling complex fracture phenomena across diverse construction material systems.